Electric activity of lumbar muscles in sport climbers - Ginszt, Michał; Berger, Marcin; Gawda, Piotr; Marczak, Milena; Ginszt, Apolinary; Majcher, Piotr (Journal of Education, Health and Sport, 2017)
Background: The synergy of all muscle groups seems to play crucial role in professional sport climbing. Climbing activity demands good balance and coordination between various parts of musculature. Unfortunately, this issue is an under-reviewed aspect in the literature. Aim: The aim of this study was to compare the endurance-fatigue characteristics in rectus abdominals (RA) and erector spinae (ES) muscles during the isometric exercises performed by professional and amateur sport climbers. Material and methods: We examined 50 healthy sport climbers (38 men, 12 women) aged 23 ± 3 years. Participants were divided into two groups: 25 professional and 25 amateur sport climbers. The International Climbing and Mountaineering Federation UIAA scale was used for classification: professional climbers > X-, amateurs < VII. The myoelectric activity of the RA and ES muscles was recorded simultaneously during isometric activity in a basic plank position. Results: Significant differences in ES and RA muscles activity, between professional climbers and amateurs, were observed during trunk muscle strength tests in a basic plank position. EMG median frequency was reduced from beginning to end of exercise (amateur climbers: RA - 23.40%, ES - 26.81%; professional climbers: RA - 19.69%, ES - 15.78%; p < 0.001). Conclusions: Difference in muscle activity between professional and amateur sport climbers suggests that rectus abdominals and erector spinae muscles plays an important role in climbing.